Machine Learning Approaches to Prognostication in Traumatic Brain Injury - Badjatia, Neeraj; Podell, Jamie; Felix, Ryan B.; Chen, Lujie Karen; Dalton, Kenneth; Wang, Tina I.; Yang, Shiming; Hu, Peter (Current neurology and neuroscience reports, 2025)
Purpose of Review This review investigates the use of machine learning (ML) in prognosticating outcomes for traumatic brain injury (TBI). It underscores the benefits of ML models in processing and integrating complex, multimodal data—including clinical, imaging, and physiological inputs—to identify intricate non-linear relationships that traditional methods might overlook. Recent Findings ML algorithms of clinical features, neuroimaging, and metrics from the autonomic nervous system enhance the early detection of clinical deterioration and improve outcome prediction. Challenges persist, including issues of data variability, model interpretability, and overfitting. However, advancements in model standardization and validation are key to enhancing their clinical applicability. Summary ML-based, multimodal approaches offer transformative potential for personalized treatment planning and patient management. Future directions include integrating digital twins and real-time continuous data analysis, reinforcing the idea that comprehensive data amalgamation is essential for precise, adaptive prognostication and decision-making in neurocritical care, ultimately leading to better patient outcomes.